2022
DOI: 10.3390/cells11050901
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids: Key Players in Inflammatory Bowel Diseases?

Abstract: Inflammatory bowel diseases (IBDs) have emerged as a public health problem worldwide with a limited number of efficient therapeutic options despite advances in medical therapy. Although changes in the gut microbiota composition are recognized as key drivers of dysregulated intestinal immunity, alterations in bile acids (BAs) have been shown to influence gut homeostasis and contribute to the pathogenesis of the disease. In this review, we explore the interactions involving BAs and gut microbiota in IBDs, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 74 publications
(100 reference statements)
0
18
0
Order By: Relevance
“…For example, BAAT, which is involved in primary bile acid biosynthesis, taurine and hypotaurine metabolism, biosynthesis of unsaturated fatty acids, peroxisome, and bile secretion pathways, was identified. Bile acids (BAs) play key roles in intestinal metabolism and cell signaling and changes in BAs have also been demonstrated to influence gut homeostasis and contribute to the pathogenesis of IBD [ 137 ]. Several BA receptors have been reported to be involved in the development of colorectal cancer, cholangiocellular carcinoma, or their association with cancer cell lines [ 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, BAAT, which is involved in primary bile acid biosynthesis, taurine and hypotaurine metabolism, biosynthesis of unsaturated fatty acids, peroxisome, and bile secretion pathways, was identified. Bile acids (BAs) play key roles in intestinal metabolism and cell signaling and changes in BAs have also been demonstrated to influence gut homeostasis and contribute to the pathogenesis of IBD [ 137 ]. Several BA receptors have been reported to be involved in the development of colorectal cancer, cholangiocellular carcinoma, or their association with cancer cell lines [ 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some studies have reported that bile acid metabolism is involved in the pathophysiology of CD. 9 , 10 , 11 , 12 , 13 , 14 The concentration of bile acids in the bile of CD patients is elevated compared with that in healthy individuals, and the production of 7α‐hydroxy‐4‐cholesterin‐3‐one (C4), a precursor of bile acids, is increased due to the malabsorption of bile acids. 25 In addition, fibroblast growth factor 19 (FGF19), which regulates bile acid synthesis, is decreased in patients with CD.…”
Section: Discussionmentioning
confidence: 99%
“… 6 It has been reported that anion exchange resins, such as cholestyramine and colestimide, improve bile acid diarrhea by adsorbing bile acids in the gastrointestinal tract, 7 and colesevelam has been shown to be effective in the management of bile acid diarrhea in patients with CD. 8 However, it has been suggested that abnormal metabolism of secondary bile acids produced in the intestinal tract promotes an inflammatory response in the intestinal epithelium and exacerbates the pathogenesis of CD 9 , 10 , 11 , 12 , 13 , 14 and that resins inhibit intestinal inflammation. 9 Recently, a secondary bile acid, 3‐oxolithocholic acid (3‐oxoLCA), was reported to inhibit TH17 cells; moreover, TH17 cell activation due to decreased 3‐oxoLCA may be involved in the pathogenesis of CD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have ascribed these changes to alterations in BAs absorptions, synthesis and bacterial modification ( Li et al, 2021a ). Furthermore, these characteristic alterations of BAs are considered to correlate with the disease severity of IBD ( Duboc et al, 2013 ; Kriaa et al, 2022 ). Recent studies have also provided evidence for the involvement of BAs in IBD-associated autophagy, apoptosis, and inflammasome pathways ( Thomas et al, 2022 ).…”
Section: High Correlation Between Dysbiosis Of Gut Microbiota and Ibdmentioning
confidence: 99%
“…Recent studies have also provided evidence for the involvement of BAs in IBD-associated autophagy, apoptosis, and inflammasome pathways ( Thomas et al, 2022 ). Meanwhile, the interactions of BAs with intestinal epithelial cells and immune cells have also been revealed, further providing novel insights into the gut microbiota-BA-host axis in the pathogenesis of IBD ( Yang et al, 2021 ; Kriaa et al, 2022 ).…”
Section: High Correlation Between Dysbiosis Of Gut Microbiota and Ibdmentioning
confidence: 99%